Precautionary Saving and Altruism - Katarina Nordblom (Uppsala University, Department of Economics, 1997)
The potential importance of the precautionary motive for saving has been noted in many studies during the last decades. This paper examines the determination of precautionary saving when people have access to intra-family risk sharing. I show that, with uncertain future income, altruism per se can induce time consistent, however, not necessarily ex ante efficient, risk sharing between risk averse spouses. The more altruistic the couple is, the closer is the solution to the efficient one. Also welfare and savings effects from social insurance turn out to be sensitive to assumptions about family structure. For risk sharing couples, the introduction of a compulsory insurance scheme may have substantially smaller effects on welfare and precautionary savings.
urn:nbn:se:uu:diva-2387
Keywords: D64; D81; J12; 330; Precautionary saving; altruism; risk sharing; marriage; intra-family insurance